Growth status, inflammation, and enteropathy in young children in Northern Tanzania - Wirth, James P.; Kitilya, Brenda; Petry, Nicolai; PrayGod, George; Veryser, Stephen; Becquey, Elodie (American Society of Tropical Medicine and Hygiene, 2019)
Recent evidence suggests that enteropathy of the gut due to environmental conditions (i.e., environmental enteropathy [EE]) in young children is negatively associated with linear growth. Using a case–control study design, we examined the potential determinants of stunting in stunted and non-stunted children 22–28 months of age. Potential determinants included inflammation biomarkers C-reactive protein, alpha-1-acid glycoprotein (AGP), and endotoxin-core antibody (EndoCAb) measured in serum samples; enteropathy markers alpha-1-antitrypsin, neopterin, myeloperoxidase (MPO) measured in stools samples; and demographic, health, feeding, and household characteristics. We also explored the determinants of EE by testing associations of composite EE scores and individual biomarkers with potential risk factors. Fifty-two percent of children (n = 310) were found to be stunted, and mean height-for-age Z scores (HAZ) were −1.22 (standard deviation [SD] ± 0.56) among non-stunted (control) children and −2.82 (SD ± 0.61) among stunted (case) children. Child HAZ was significantly (P < 0.05) and inversely associated with AGP, and child stunting was significantly positively associated (P < 0.05) with low dietary diversity, severe household hunger, and absence of soap in the household. Alpha-1-acid glycoprotein and EndoCAb concentrations were also significantly higher (P < 0.05) among children in households with no soap. Our study documented a seemingly localized cultural practice of young children (25%) being fed their dirty bathwater, which was associated with significantly higher concentrations of MPO (P < 0.05). Alpha-1-acid glycoprotein showed the most consistent associations with child growth and hygiene practices, but fecal EE biomarkers were not associated with child growth. The lack of retrospective data in our study may explain the null findings related to fecal EE biomarkers and child growth.